К вопросу о семантических функциях поствербов в английском языке - Клиюнайте, Ина (Kalbotyra, 1987)
The article deals with the semantic functions of the English postverb out with reference to the aspectual meanings of units ‘verb–postverb’ of the type burn out, smell out, go out. Our analysis shows that this postverb changes the durative aspect of the base verb into terminative and adds the meaning of certain modes of action to the base verb.